Physical Exercise as Leisure Activities in Youth's Lives - M.C. Nanu; L. Brabiescu Calinescu; D. Pascu; M.A. Cosma (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics, 2023)
Despite the known benefits of physical activity, there is a worldwide trend towards less daily physical activity. According to the latest Eurobarometer, 63% of the population of our country never do physical exercises or sports, placing them at the bottom of the ranking of EU countries. The present study aims to identify the share of physical activities in the free time budget of young people. Thus, it is desired that, through a sociological investigation, to investigate whether young people in the Oltenia area actively spend their free time. Methods. The research was carried out between April and June 2022 and consisted of the development, transmission, and interpretation of the data of a questionnaire applied in the online system, on the google.doc platform. The questionnaire contained 15 items referring to the free time of young people, which were answered by 71 young people under conditions of anonymity. Results. Most respondents exercise occasionally in their free time, with the frequency of exercise positively correlating with the perception of physical appearance (r=0.45, p<0.01).